2000
DOI: 10.1097/00006454-200008000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis in human immunodeficiency virus-infected and human immunodeficiency virus-exposed children in New York City

Abstract: During a period of high tuberculosis incidence in NYC, 3% of HIV-infected children in our cohort had tuberculosis, higher than the rate in uninfected children born to HIV-positive mothers in the same cohort. Because of this association, HIV-infected children with pulmonary illness should be tested for tuberculosis; and all children with tuberculosis should be tested for HIV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 16 publications
4
16
0
Order By: Relevance
“…In one large paediatric HIV clinic in London, UK, there was an average of two children with HIV per year who presented with active TB over a 15 year period (18/328, 5.5% of HIV infected patients were treated for active TB) [22] and in a US cohort of nearly 1500 HIV infected children, TB disease was found 3%, with an incidence of 0.61 per 100 child-years [23]. In contrast, in high prevalence countries, the incidence of TB disease in HIV positive children is much higher.…”
Section: Epidemiology Of Paediatric Hiv/tb Diseasementioning
confidence: 99%
“…In one large paediatric HIV clinic in London, UK, there was an average of two children with HIV per year who presented with active TB over a 15 year period (18/328, 5.5% of HIV infected patients were treated for active TB) [22] and in a US cohort of nearly 1500 HIV infected children, TB disease was found 3%, with an incidence of 0.61 per 100 child-years [23]. In contrast, in high prevalence countries, the incidence of TB disease in HIV positive children is much higher.…”
Section: Epidemiology Of Paediatric Hiv/tb Diseasementioning
confidence: 99%
“…15,27-29,32-37 HIV-infected children have an increased risk of developing pulmonary TB and of complicated or disseminated disease compared to uninfected children. [32][33][34] Co-infection with M. tuberculosis and HIV results in more rapid deterioration of immune dysfunction, viral replication, and HIV progression, and more frequent, severe other infections. [35][36][37][38] Symptoms, and signs of TB may be chronic, and nonspecific, including weight loss, failure to thrive, fever or persistent respiratory symptoms.…”
Section: Mycobacterial Infectionsmentioning
confidence: 99%
“…Overall, two (6%) of 33 cases were co-infected with HIV; one of these was a previously reported (suspect) TB case, and the other was a confirmed case that had been undetected by alternative surveillance. Numerous studies have emphasized the benefits of sharing information between healthcare agencies, 11,26,27,32 but this strategy can be difficult to implement due to patient confidentiality. 27 Previous studies have demonstrated under-notification of TB, ranging from 12% to 94%, in patients with known HIV infection or AIDS.…”
Section: Discussionmentioning
confidence: 99%
“…4,8,9 The NYC DOH and the Centers for Disease Control and Prevention (CDC) have also sponsored two ongoing active surveillance programs to assess co-infection with HIV and TB in children: the Pediatric Spectrum of Disease and Pediatric AIDS Surveillance. 10,11 To assess the completeness of reporting of pediatric TB cases to the NYC DOH Bureau of TB Control from January 1993 to December 1995, hospital-based alternative surveillance was developed to detect previously unreported cases of TB in children in our targeted surveillance area. The TB and TB/HIV cases identified by alternative surveillance were compared with cases previously reported to the NYC DOH during the same time period.…”
mentioning
confidence: 99%